2006
DOI: 10.1063/1.2194019
|View full text |Cite
|
Sign up to set email alerts
|

Boundary slip and wetting properties of interfaces: Correlation of the contact angle with the slip length

Abstract: Correlations between contact angle, a measure of the wetting of surfaces, and slip length are developed using nonequilibrium molecular dynamics for a Lennard-Jones fluid in Couette flow between graphitelike hexagonal-lattice walls. The fluid-wall interaction is varied by modulating the interfacial energy parameter epsilonr=epsilonsfepsilonff and the size parameter sigmar=sigmasfsigmaff, (s=solid, f=fluid) to achieve hydrophobicity (solvophobicity) or hydrophilicity (solvophilicity). The effects of surface chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
91
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 86 publications
13
91
1
3
Order By: Relevance
“…We attribute the reverse dependence of L s $ T to the distinct affinities of silica and graphene for hydrocarbons. This result supports the insights of Voronov et al [60], who studied the correlation of boundary slip and wetting properties using Couette flow simulations (NEMD) of LJ particles by varying the relative affinities and suggested that the temperature exhibits a very complex effect on the slip length, depending on the intermolecular interactions. At a given pressure gradient, an increase in temperature still enhances the flow of liquid alkanes in an organic slit, even though the slip length is becoming smaller.…”
Section: Effect Of Temperaturesupporting
confidence: 89%
See 1 more Smart Citation
“…We attribute the reverse dependence of L s $ T to the distinct affinities of silica and graphene for hydrocarbons. This result supports the insights of Voronov et al [60], who studied the correlation of boundary slip and wetting properties using Couette flow simulations (NEMD) of LJ particles by varying the relative affinities and suggested that the temperature exhibits a very complex effect on the slip length, depending on the intermolecular interactions. At a given pressure gradient, an increase in temperature still enhances the flow of liquid alkanes in an organic slit, even though the slip length is becoming smaller.…”
Section: Effect Of Temperaturesupporting
confidence: 89%
“…The upward trend of slip length upon heating is qualitatively consistent with the results of a quartz-octane system [41] but opposite to that observed for OM-octane (Fig. 6), which demonstrates that the dependence of slip length on temperature is very complicated, as suggested by Voronov et al [60].…”
Section: Effect Of Temperaturesupporting
confidence: 85%
“…Thus, as increasing the number density of the solid wall, the decrease of the corrugation play the dominant role, resulting in the increase of the boundary slip. The temperature of the confined fluid represents the thermal vibration of the fluid molecules, which can reduce the fluid-solid binding if the temperature is high (Voronov et al 2006;Li 2009b). To obtain the identical equilibrium pressure of the fluid for different fluid temperature, the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fluid adsorption on solid surfaces is generally determined by the ratio of fluid-wall binding energy to temperature, " fw =kT [17][18][19][20][21][22]. This ratio expresses the competition between the fluid-wall binding strength and the kinetic energy of the fluid.…”
mentioning
confidence: 99%